PENGARUH DIGITAL MARKETING DAN ONLINE CONSUMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN GADGET SMARTPHONE DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA KEMENTERIAN PERTANIAN RI - Fadlan Pramudito (2022)
The purpose of this thesis research is to determine the effect of digital marketing, online consumer reviews on consumer trust and purchasing decisions. The population in this study is. Employee of the Director General of Livestock and Animal Health of the Indonesian Ministry of Agriculture. The sample size was taken as many as 75 respondents, with probability sampling method, especially simple random sampling. Data was collected through the distribution of questionnaires. The analytical technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that (1) Digital marketing has no effect on consumer trust with a path coefficient value of -0.003 (2) online consumer reviews affect consumer trust with a path coefficient value of 0.848 (3) digital marketing affects purchasing decisions with a coefficient value path of 0.441 (4) online consumer review has an effect on purchasing decisions with a path coefficient value of 0.353 and (5) consumer trust has no effect on purchasing decisions with a path coefficient value of -0.051.